A community based seroprevalence of SARS‐CoV‐2 antibodies in Somali Region, Eastern Ethiopia - Solomon Yared; Tsegalem Abera; Seid Mohammed Ali; Abdifatah Muktar Muhummed; Mohammed Ibrahim; Abdulahi Hussen; Jan Hattendorf; Jakob Zinsstag; Rea Tschopp (Immunity, Inflammation and Disease)
Abstract Background Coronavirus disease 19 (COVID‐19) is life‐threatening infectious disease caused by SARS‐CoV‐2 virus that caused a global pandemic. SARS‐CoV‐2 has been widely transmitted throughout Ethiopia, with over 501,060 cases confirmed and 7574 deaths until November 2023. This study assessed for the first time the seroprevalence SARS‐CoV‐2 in the general population of the Somali Region during the COVID‐19 pandemic. Methods A cross‐sectional study design was conducted from May to June 2021 in 14 districts of Somali Region. Blood samples were collected in 820 participants in addition to administering a questionnaire that included sociodemographic characteristics and history of clinical symptoms of COVID‐19. Blood samples were tested for the presence or absence of anti‐SARS‐CoV‐2 using a commercial Enzyme‐Linked Immunosorbent Assay (ELISA) kit (Euroimmun). Results Overall, 477 (58.2%) were male and 343 (41.8%) were female. The majority of the participants (N = 581; 70.9%) were between 18 and 34 years old and not vaccinated against COVID‐19 (N = 793; 96.7%). The overall seroprevalence of SARS‐CoV‐2 antibodies was 41.7% (95% CI: 33.3%–47.6%). The highest prevalence was found in Goljano district (70%) and the lowest in Gunagado district (22.5%). Only age was found to be associated with COVID‐19 seropositivity. Conclusion Prevalence of SARS‐CoV‐2 antibodies was the highest ever reported in Ethiopia, indicating that a large proportion of the population had been infected 14 months after the start of the outbreak in the country. Such studies are important to swiftly reassess and improve specific COVID‐19 preventive and control measures to reduce transmissions within the community in a given setting.